Effect of a Water Soluble Organic Additive on Growth Performances, Hematological Parameters and Cost Effectiveness in Broiler Production - Saha, M; Chowdhury, SD; Hossain, ME; Islam, MK; Roy, BJ (Progressive Agriculture, 2013)
An experiment was conducted with 144 broiler chicks (Cobb 500) from day-old to five weeks of age to investigate the efficacy of a water additive in broiler production. The chicks were randomly distributed into four different treatments namely T1 (control), T2 (water additive as per recommended level of the manufacturer), T3 (25% less than the recommendation) and T4 (25% more than the recommendation). Broiler growth performances and hematological parameters were studied and cost effectiveness of the application of such water additive was determined. There was an improvement in both body weight and FCR due to addition of water additive although all productive performances in birds receiving treatments showed no significant differences from the control. Among the hematological parameters, lower values were obtained for mean cell volume and mean cell hemoglobin, although only the former (mean cell volume) of the treated groups differed significantly (P<0.05) from the control. However, all levels of water additive increased profit in comparison with the control but addition of the additive at a rate 25% less than the recommendation appeared to be most profitable and cost effective. It was therefore concluded that the water additive tested in this study may be applied 25% less than the usual recommendation. It also suggests that any additive considered for poultry, must undergo trial for determining efficacy as well as its cost effectiveness for application. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16754 Progress. Agric. 21(1 & 2): 73 - 82, 2010